Modeling and Simulation as a Tool to Bridge Efficacy and Safety Data in Special Populations. (27th February 2013) - Harnisch, L; Shepard, T; Pons, G; Della Pasqua, O
Abstract : The registration and approval of novel medicines have traditionally been based on evidence arising from large prospective trials. Such an approach is often not possible or unsuitable to evaluate the benefit‐risk balance in special populations (e.g., children, ethnic groups, rare diseases). Inferences by modeling and simulation can play a major role in evidence synthesis. A framework is proposed that promotes its acceptability and the basis for decision making during development, registration, and therapeutic use of drugs. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e28; doi:10.1038/psp.2013.6 ; advance online publication 27 February 2013